Keadilan Agraria dalam Islam: Telaah Historis Kebijakan Agrariya Islam Priode Awal - Fatmawati Fatmawati (LP3M KH Yazid Karimullah Institute, 2021)
The land crisis is crucial and a scourge for state sovereignty. This is a problem that has plagued Islam historically with the Qur'an and Hadith having established the concept of agrarian justice through the laws and ethics taught by the Prophet as practiced by the salaf. This paper seeks to present kemali in the reader's memory how agrarian problems in the golden age of Islam can be unraveled and handled. The results of this search obtained several points of conclusion as follows, pertmama, the division of the agrarian sector in the early days of Islam was divided on the basis of consideration of common needs, this is like public facilities (hima), then the division on the basis of the needs and conditions of the ummah such as the division of those who have just converted to Islam which some economically and faith are still weak.Second, the termination of disputes in the agrarian sector at that time was based heavily on falid and differentiated evidence to achieve benefits for both parties, as in the case of disputes over fruit products from trees planted illegally on other people's land